The Buck, the Black, and the Existential Hero : Refiguring the Black Male Literary Canon, 1850 to Present - Haile, James B., 1979- (Book collections on Project MUSE., 2020)
"The Buck, the Black, and the Existential Hero: Refiguring the Black Male Literary Canon, 1850 to Present combines philosophy, literary theory, and jazz studies with Africana studies to develop a theory of the black male literary imagination. In doing so, it seeks to answer fundamental aesthetic and existential questions: How does the experience of being black and male in the modern West affect the telling of a narrative, the shape or structure of a novel, the development of characters and plot lines, and the nature of criticism itself? James B. Haile argues that, since black male identity is largely fluid and open to interpretation, reinterpretation, and misinterpretation, the literature of black men has developed flexibility and improvisation, termed the "jazz of life." Our reading of this literature requires the same kind of flexibility and improvisation to understand what is being said and why, as well as what is not being said and why. Finally, the book attempts to offer this new reading experience by placing texts by well-known authors, such as Frederick Douglass, Ralph Ellison, and Colson Whitehead, in conversation with texts by those who are less well known and those who have, for the most part, been forgotten, in particular, Cecil Brown. Doing so challenges the reader to visit and revisit these novels with a new perspective about the social, political, historical, and psychic realities of black men." --